The Effect of Islamic Values-Based Character Education on Early Childhood Social Emotional Development - Saona Saona (Sekolah Tinggi Agama Islam Kuningan (STAIKuningan), 2025)
This study aims to examine the effect of Islamic values-based character education on early childhood social-emotional development. In this study, a qualitative approach was used with an analytic descriptive method, which involved interviews with educators and parents, direct observation in the classroom, as well as questionnaires filled out by educators. The results showed that the implementation of Islamic values-based character education had a significant positive impact on children's socio-emotional development. Children who received this education showed improvements in their empathy, cooperation and emotion management skills, which were reflected in their daily social interactions, both at school and at home. However, challenges faced in its implementation include limited time to explore the materials, as well as the need for further training for educators. This study provides recommendations for integrating Islamic-based character education more intensively in the early childhood education curriculum and providing support to parents in teaching these values at home. Overall, this study shows that Islam-based character education plays an important role in shaping children's socio-emotional behavior, which supports balanced personal development.